"I just couldn't cope with it, you know? I just couldn't believe that she was gone": the portrayal of co-victims' grief in true crime podcasts about missing (but presumed killed) women - Slakoff, Danielle C. (Journal of family violence, 2024)
Purpose: True crime, a subset of crime-focused media that turns real cases into entertainment for the public’s consumption, regularly features co-victims within their narratives. To our knowledge, no studies have examined how co-victims (i.e., family members and friends of the victims and/or perpetrators) of intimate partner violence are portrayed. Co-victims often experience intense grief after their loved one goes missing or is killed, but their public journeys through the grief process have not yet been examined through a media lens. As such, the goal of this study is to center co-victims’ portrayals by examining how their grief was portrayed. Method: Using Kübler-Ross and Kessler’s six stages of grief as the primary codes, the researchers used directed qualitative content analysis to examine co-victims’ grief in three seasons of true crime podcasts focused on still missing (but presumed dead) women. In all three cases, the victims are presumed killed by their former or current intimate partner. Results: Throughout the three true crime podcast seasons, the co-victims’ experiences with grief are portrayed as complex, with all six stages represented in some fashion. However, the acceptance and ‘meaning’ stages of grief were the most commonly depicted, with co-victims often describing their need to commemorate and remember their loved one (sometimes via participating in media portrayals). Conclusions: We discuss clinical interventions that may benefit co-victims of crime, as well as discuss possible ways that true crime content creators can better support co-victims featured in their stories.